ChemInform Abstract: An Intramolecular Pyranone Diels—Alder Cycloaddition Approach to Cannabinol. Issue 39 (23rd September 2014) - Fan, Fangfang; Dong, Jingjing; Wang, Jinqian; Song, Lina; Song, Chuanjun; Chang, Junbiao
Abstract The key step in the synthesis of cannabinol (V) is the intramolecular pyranone Diels—Alder cycloaddition to construct the benzo[c]chromene framework.